Pelatihan Label Kemasan Produk sebagai Upaya Peningkatan Kualitas Produk UMKM Cahaya di Dusun Krajan Desa Giripurno, Kota Batu - Munarko, Hadi; Dewantara, Daffa (Kifah: Jurnal Pengabdian Masyarakat, 2024)
The development of UMKM in Giripurno Village has not been accompanied by an increase in the quality of the products produced, especially in the use of labels on food product packaging. Socialization of the importance of labeling and label assistance in Krajan was carried with the aim of increasing public knowledge regarding the importance of using labels and improving the quality of food products by improving packaging labels. which complies with Badan Pengawas Obat dan Makanan (BPOM) regulations. The method used in this activity is socialization of the importance of labeling and assistance in making labels. The lecture was carried out by delivering material related to the importance of labeling on food products. In the presentation of this material there were three main topics of discussion, namely the meaning of labels, the criteria included on labels and label requirements, as well as the importance of using labels on food products. As for label assistance, this is done by discussing with UMKM owner, following the production process, and the label making process with the help of the Canva application. The socialization carried out among dasa wisma members resulted in increased knowledge regarding labels on food products, so it is hoped that this will make the process of making labels easier and avoid mistakes in understanding labels on products. The socialization and mentoring activities that have been carried out have resulted in new knowledge for the members of the Krajan’s dasa wisma members and also produced a new label for UMKM Cahaya.